Fatigue resistance of pipe-to-plate welded joint under in-phase and out-of-phase combined bending and torsion. (October 2015) - Frendo, Francesco; Bertini, Leonardo
Highlights: The fatigue resistance of a welded joint is experimentally investigated. A new experimental apparatus for combined bending and torsion is described. Results were analysed by the nominal stress method. The endurances under proportional and nonproportional loading are discussed. The fatigue endurances obtained by three different multiaxial criteria are compared. Abstract: The fatigue resistance of a pipe-to-plate welded joint was investigated under combined in-phase and out-of-phase (changing principal directions) bending and torsion. The specimen consisted of a pipe having 64 mm outer diameter and 10 mm thickness, which is joined by fillet welding to a 25 mm thickness plate. The pipe and plate were made of S355 steel and the joint was not subjected to any after welding relieve treatment. This work represent an extension of a previous work by the authors, in which the fatigue resistance of the same joint was investigated under bending, torsion and combined in-phase loading. A new experimental arrangement, making use of two independent hydraulic actuators, was developed to have the possibility of making out of phase tests. Four series of tests were then carried out in the life range 10 5 – 2 · 10 6, with two bending to torsion ratios (i.e. σ / τ = 3.25 and σ / τ = 0.88 ) and two load ratios (i.e. R = - 1 and R = 0 ). For the examined joint, failures originated from the weld root, where a severe notch is present. The results confirmed a lower fatigue endurance in case of out-of-phase loading, by a factor ranging from 2 to 8 depending on the number of cycles and on the adopted failure hypothesis.